2020
DOI: 10.1002/pbc.28223
|View full text |Cite
|
Sign up to set email alerts
|

Kidney‐sparing whole abdominal irradiation in Wilms tumor: Potential advantages of VMAT technique

Abstract: Purpose To present a preliminary clinical experience and a dosimetric comparison of kidney‐sparing volumetric modulated arc therapy (VMAT) with three‐dimensional conformal radiotherapy (3D‐CRT) for whole abdominal irradiation (WAI), in the setting of Wilms tumor (WT) treatment. Materials and methods From a total of 20 consecutive WT cases treated with adjuvant irradiation, seven were submitted to WAI with VMAT. Renal function and survival rates were evaluated, and, for comparison purposes, similar VMAT and 3D‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
(103 reference statements)
0
9
0
Order By: Relevance
“…CBCT, daily kV port films) during radiotherapy, of which 40 studies reported on applied margin sizes. Four studies reported that no IGRT was used [27][28][29][30], and in two studies IGRT techniques were not applicable as patients were not treated with radiotherapy [31,32]. In the remaining 65 studies the use of IGRT techniques during radiotherapy was not explicitly reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CBCT, daily kV port films) during radiotherapy, of which 40 studies reported on applied margin sizes. Four studies reported that no IGRT was used [27][28][29][30], and in two studies IGRT techniques were not applicable as patients were not treated with radiotherapy [31,32]. In the remaining 65 studies the use of IGRT techniques during radiotherapy was not explicitly reported.…”
Section: Resultsmentioning
confidence: 99%
“…Most commonly reported margins types were GTV-CTV and CTV-PTV margins for thoracic [44, (Fig. 2A), abdominal [15,18,30,41,45,[50][51][52][53][54][55][56]60,[62][63][64]66,70,73,74,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94] (Fig. 2B), spinal [43,46,48,63,82, (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…29 Of note, successful births from autotransplanted ovarian tissue harvested from young pediatric female cancer patients have been reported. 30 Dosimetric analyses demonstrate OAR dose reduction for flank, 27 WART, 31 liver, 20 and WLI. 17 While benefit of IMRT/IMAT will take years to demonstrate, currently there is no consensus among radiation oncologists in COG and SIOP regarding target volume delineation and RT techniques for flank, WART and WLI.…”
Section: Oncofertilitymentioning
confidence: 98%
“…Modulated RT, specifically IMRT and IMAT, has been shown to improve the therapeutic ratio for WT by focusing desired radiation dose to the tumor target and minimizing dose to adjacent OARs (Figure 2). Dosimetric analyses demonstrate OAR dose reduction for flank, 27 WART, 31 liver, 20 and WLI 17 . While benefit of IMRT/IMAT will take years to demonstrate, currently there is no consensus among radiation oncologists in COG and SIOP regarding target volume delineation and RT techniques for flank, WART and WLI 32 .…”
Section: Knowlegde Gaps and Opportunitiesmentioning
confidence: 99%
“…A guideline for translation of the target volumes of the conventional opposing photon beams into highly conformal volumes for flank irradiation has been added to the UMBRELLA SIOP-RTSG 2016 protocol [60]. Similarly, the application of modern techniques to whole-abdomen and whole-lung irradiation may contribute to a better adjacent heathy tissue protection [61,62].…”
Section: Table 5 Summary Of Radiotherapy Recommendations For Abdomina...mentioning
confidence: 99%